Pengaruh Lebar Lajur Lalu Lintas Terhadap Kecepatan Kendaraan Pada Jalan Perkotaan - Kurniati, Titi (Universitas Andalas, 2024)
The design of the road lane width plays an important role in controlling vehicle speed. Controlled vehicle speed will have an impact on traffic safety. The purpose of this study was to determine the effect of traffic lane width on average operating speed. Traffic lane width and vehicle speed on urban road sections were analyzed using 2019 data collected through recording using a video camera. A total of 12,273 instantaneous vehicle speed data were collected on four road sections with similar facilities and traffic conditions but different lane widths in the urban area of ​​Padang City. Data on the relationship between speed and lane width are presented descriptively statistically. To test the difference in average operating speed of each traffic lane width, the ANOVA approach was used. Meanwhile, to test the operating speed between two (2) lane widths, a hypothesis test was carried out at a 95% confidence level. The results of the ANOVA test concluded that there was a significant difference in operating speed with different traffic lane widths. Likewise, the results of the hypothesis test conclusion showed that there was a significant difference in average operating speed between lane widths of 3.25m, 3.50m, 3.75m and 4.15m.